KONTRIBUSI DAYA LEDAK OTOT LENGAN DAN KOORDINASI MATA-TANGAN TERHADAP KETEPATAN SERVIS ATAS BOLAVOLI PADA EKSTRA KURIKULER DI SMP NEGERI 19 PALEMBANG - Lestari, Hikmah (STKIP Pasundan, 2018)
The problem in this study is the low service accuracy of volleyball in extra-curricular students at Palembang 19 Public Middle School. This study aims to determine the contribution between arm muscle explosive power and hand eye coordination to the accuracy of service for volleyball in extra-curricular students at SMP Negeri 19 Palembang. This research method is a correlational method. The study population was all students who took extra curricular volleyball at SMP Negeri 19 Palembang, who registered and participated in the training totaling 35 people consisting of 22 sons and 13 daughters, while the sample was taken by purposive sampling so that a sample with 22 player people. The place of the research was in the volleyball court of SMP Negeri 19 Palembang, while the time of the study was December 2017. Data on the explosive power of the arm muscles using the test, one ball medicine ball put (Haag and Dassel, 1981: 217) hand eye coordination was taken using the coordination test hand eye (Haag and Dassel, 1981: 2) and the accuracy of the top service is taken by conducting a service test on (Yunus 1992: 302) The data analysis technique of this study uses multiple correlation analysis techniques and finally followed by the contribution test. The results of the data analysis show that: There is a contribution between the explosive power of the arm muscles and the accuracy of the upper service, There is a contribution between eye hand coordination and the accuracy of the upper service, There is a contribution between the explosive power of the arm muscles and eye hand coordination together with the service accuracy of the volleyball at SMP Negeri 19 Palembang. So it can be concluded that the arm muscle explosive power and eye-hand coordination contribute significantly to the accuracy of service for volleyball athletes at SMP Negeri 19 Palembang.